Epigallocatechin gallate facilitates extracellular elastin fiber formation in induced pluripotent stem cell derived vascular smooth muscle cells for tissue engineering. (February 2022) - Ellis, Matthew W.; Riaz, Muhammad; Huang, Yan; Anderson, Christopher W.; Luo, Jiesi; Park, Jinkyu; Lopez, Colleen A.; Batty, Luke D.; Gibson, Kimberley H.; Qyang, Yibing
Abstract: Tissue engineered vascular grafts possess several advantages over synthetic or autologous grafts, including increased availability and reduced rates of infection and thrombosis. Engineered grafts constructed from human induced pluripotent stem cell derivatives further offer enhanced reproducibility in graft production. One notable obstacle to clinical application of these grafts is the lack of elastin in the vessel wall, which would serve to endow compliance in addition to mechanical strength. This study establishes the ability of the polyphenol compound epigallocatechin gallate, a principal component of green tea, to facilitate the extracellular formation of elastin fibers in vascular smooth muscle cells derived from human induced pluripotent stem cells. Further, this study describes the creation of a doxycycline-inducible elastin expression system to uncouple elastin production from vascular smooth muscle cell proliferative capacity to permit fiber formation in conditions conducive to robust tissue engineering. Graphical abstract: Unlabelled Image Highlights: Epigallocatechin gallate addition leads to extracellular elastin formation in vitro. Epigallocatechin gallate-treated tissue rings appear to display enhanced elasticity. Doxycycline-inducible construct for ectopic expression of elastin mRNA and protein. Use of doxycycline and epigallocatechin gallate produces elastin under high serum. Applied to stem cell-derived culture for future elastin enriched vessel engineering.